Fosfolipase C delta 4 humana (hPLCδ4): uma proteína envolvida na proliferação e na diferenciação celular - Marianna Kunrath Lima (2018)
Ca2+ is an important second messenger within cells, and it is involved in many cellular processes, like death and proliferation. The raise in intracellular Ca2+ levels can be due to the generation of inositol 1, 4, 5-trisphosphate (InsP3), which is a product of phosphatidylinositol 4, 5-bisphosphate (PIP2) hydrolysis by phospholipases C (PLCs) that leads to Ca2+ release by InsP3R. Ca2+ release can occur in both cytosol and nucleus, via PLCs, but little is known about these enzymes’ activation in the nucleus. The objective of this work was to study PLCδ4 function in mesenchymal cells. This protein, which has not been extensively studied, has been pointed out as nuclear and it has a possible role in proliferative processes. In this thesis, two human mesenchymal cell models were used to phenotypically characterize human PLCδ4 (hPLCδ4): SK-HEP-1 tumor cells and human adipose-derived stem cells (hASC). In SK-HEP-1, hPLCδ4 silencing by siRNA reduced cell proliferation, without cell death increase, but with an increase in the percentage of cells on G1 and G2/M cell cycle phases and reduction in the expression of cyclins A, B1 and H. For hASC, initially we proceeded to the subcellular localization of hPLCδ4, using confocal microscopy. This protein showed to be mainly nuclear, being the nuclear presence of hPLCδ4 confirmed by cell fractionation. When hASC were submitted to cell differentiation, it was observed an increase in PLCδ4 protein expression after adipogenic differentiation, but this increase was not observed for cells that were incubated with osteogenic inducers. hASC PLCδ4 knockdown, as for SK-HEP-1, showed reduced cell proliferation, without cell death increase. However, for silenced cells it was observed an increase of cells on G1 and a reduction of cells on interphase and G2/M. PLCδ4 silencing increased the percentage of senescent cells in hASC, what could explain the reduction in cell proliferation. Thus, these data show that human PLCδ4 is in involved in cellular differentiation and cellular proliferation, being these processes possibly mediated by nuclear Ca2+.